Hayabusa2-Ryugu proximity operation planning and landing site selection. (October 2018) - Yamaguchi, Tomohiro; Saiki, Takanao; Tanaka, Satoshi; Takei, Yuto; Okada, Tatsuaki; Takahashi, Tadateru; Tsuda, Yuichi
Abstract: This paper presents the robust planning of the Hayabusa2-Ryugu proximity operation and landing site selection process considering unknown asteroid environment and the spacecraft constraints. The proximity operation scenario is described together with the relationship between the selection process and the in-situ observation. The mission constraints are summarized for the possible asteroid environment, including the rotation state, thermal condition and gravity. Highlights: Hayabusa2 proximity operation and "joint" landing site selection process are summarized. A strategy of Ryugu proximity operation is discussed for a surface sampling. Joint landing site selection process is constructed for sampling and landing sites.